Differential tissue tropism of Trypanosoma cruzi strains: an in vitro study - Luciana O Andrade; Lúcia MC Galvão; Maria de Nazareth SL Meirelles; Egler Chiari; Sergio DJ Pena; Andrea M Macedo (Memorias do Instituto Oswaldo Cruz, 2010)
We have previously demonstrated selection favoring the JG strain of Trypanosoma cruziin hearts of BALB/c mice that were chronically infected with an equal mixture of the monoclonal JG strain and a clone of the Colombian strain, Col1.7G2. To evaluate whether cell invasion efficiency drives this selection, we infected primary cultures of BALB/c cardiomyocytes using these same T. cruzi populations. Contrary to expectation, Col1.7G2 parasites invaded heart cell cultures in higher numbers than JG parasites; however, intracellular multiplication of JG parasites was more efficient than that of Col1.7G2 parasites. This phenomenon was only observed for cardiomyocytes and not for cultured Vero cells. Double infections (Col1.7G2 + JG) showed similar results. Even though invasion might influence tissue selection, our data strongly suggest that intracellular development is important to determine parasite tissue tropism.